Very early discharge of LOw-Risk ST elevation myocardial infarction patients after successful primary percutaneous coronary intervention (VEDLOR-STEMI) study - Refai Showkathali; Radhapriya Yalamanchi; Aishwarya Mahesh Kumar; Sengottuvelu Gunasekaran; Abraham Oomman (Indian Heart Journal, 2025)
This VEDLOR-STEMI study assessed the safety and efficacy of very-early discharge (VED- ≤ 48 h) after primary percutaneous coronary intervention (PPCI) for patients with ST elevation myocardial infarction who are considered low risk and compared their outcome with low-risk patients who had standard discharge protocol. No major adverse cardiac events (MACCE) occurred within 6 months. Minor complications, like access site pain were managed without readmission. High patient satisfaction (97.3 %) was noted, with 48 % actively utilizing a hotline for queries. VED post-PPCI appears feasible and safe with appropriate discharge protocols and follow-up.